Analisis City Branding dalam Pengembangan Destinasi Pariwisata Kabupaten Jayapura - Ari Bawanti (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2016)
Jayapura district is a district located in the province of Papua. Unidirectional on the vision and mission of